Positive electrode material and preparation method thereof, positive plate, battery and power utilization device
By covering Co2+ and conductive polymer on the surface of the ternary NCM811 positive electrode material, the modified ternary NCM material is formed, which solves the problem of unstable material structure, improves the cycling performance of the battery and the peel strength of the electrode, and enhances the safety and conductivity of the battery.
Patent Information
- Application Number
- CN202411595959.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-11-11
AI Technical Summary
The ternary NCM811 positive electrode material has a structural instability due to a high proportion of Ni elements, which affects the cycling performance and safety of the battery.
By mixing the ternary NCM material with Co2+ and conductive polymer material, a modified ternary NCM material is formed with a Co2+/conductive polymer surface coated.
This method not only improves the cycling performance and safety of the battery, but also enhances the peel strength of the electrode sheet between the positive electrode material and the foil, achieving a coordinated improvement of electrical conductivity and structural stability.
Smart Images

Figure CN119673987A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a positive electrode material and a preparation method thereof, a positive electrode sheet, a battery and an electrical device. Background Art
[0002] With the rapid development of the new energy industry, society's demand for high energy density of power batteries is also increasing. Therefore, improving the energy density of lithium-ion batteries has become the focus of current attention. At present, ternary high-nickel material NCM has gradually replaced traditional LCO materials and become the first choice for lithium battery positive electrode materials.
[0003] The ternary NCM material is composed of Ni, Co, and Mn elements. Ni can increase the capacity of the battery; Co can effectively stabilize the layered structure of the ternary material and inhibit the problem of cation mixing in the material; the presence of Mn can reduce costs. At the same time, because it does not participate in chemical reactions during the charge and discharge cycle, it can stabilize the material structure and increase battery safety. The NCM811 positive electrode material contains a high proportion of 80% Ni, which can easily lead to structural instability. Therefore, how to improve the structural stability of the material while ensuring high capacity has become a top priority. Summary of the invention
[0004] The purpose of the present invention is to provide a positive electrode material and a preparation method thereof, a positive electrode sheet, a battery and an electrical device to improve the cycle performance of the battery.
[0005] To achieve the above purpose, the technical solution provided by the present invention is:
[0006] The first aspect of the present application provides a positive electrode material, wherein the positive electrode material comprises a ternary NCM material, wherein the surface of the ternary NCM material is coated with Co 2+ / conductive polymer material to form a modified ternary NCM material.
[0007] The second aspect of the present application provides a method for preparing a positive electrode material, wherein a modified ternary NCM material is prepared by mixing and reacting a ternary NCM, a cobalt-containing material and a conductive polymer.
[0008] To optimize the above technical solutions, the specific measures taken also include:
[0009] The reaction process is to mix the reaction raw materials ternary NCM, cobalt-containing materials and conductive polymer in water and heat them at a high temperature of 180°C.
[0010] The reaction temperature is -200°C and the reaction time is 20-24h.
[0011] The conductive polymer is at least one of poly(3,4-ethylenedioxythiophene), polyaniline, polypyrrole and poly(p-phenylene glycol).
[0012] Preferably, the conductive polymer is poly(3,4-ethylenedioxythiophene), the mass ratio of the ternary NCM to poly(3,4-ethylenedioxythiophene) is in the range of 30 to 34:1, and Co is formed on the surface of the ternary NCM material. 2+ / PEDOT.
[0013] The cobalt-containing material is at least one of cobalt sulfate, cobalt chloride, cobalt hydroxide and cobalt carbonate.
[0014] Preferably, the cobalt-containing material is cobalt sulfate, and the mass ratio of the ternary NCM to CoSO4.7H2O is in the range of 16 to 20:1.
[0015] The third aspect of the present application provides a positive electrode plate, which includes a positive electrode active material, and the positive electrode active material includes the positive electrode material described in the first aspect of the present application or the positive electrode material prepared by the method described in the second aspect of the present application.
[0016] The fourth aspect of the present application provides a battery, which adopts the positive electrode plate described in the third aspect of the present application.
[0017] The fifth aspect of the present application provides an electrical device, which uses the battery described in the fourth aspect of the present application.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] The positive electrode material of the present invention comprises a surface coated with Co 2+ / modified ternary NCM materials of conductive polymer materials, Co 2 + The introduction of stabilizes the structure of the ternary NCM material, thereby improving the safety of the battery; the introduction of conductive polymers can improve the conductivity of the material.
[0020] At the same time, the present application also found that the pole piece peeling strength between the positive electrode material and the foil was improved by introducing the conductive polymer. 2+ The composite of conductive polymer on ternary NCM material not only improves the battery cycle performance, but also enhances the pole piece peeling strength. 2+ The optimization effects of the two on battery performance achieve a synergistic enhancement effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 : Schematic diagram of the preparation process of the present invention.
[0022] Figure 2 : The Co-coated 2+SEM image of NCM811 modified with / PEDOT. DETAILED DESCRIPTION
[0023] The above contents of the present invention are further described in detail below in the form of embodiments, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following embodiments, and all technologies realized based on the above contents of the present invention belong to the scope of the present invention.
[0024] The experimental methods used in the following examples are all conventional methods unless otherwise specified, and the reagents, methods and equipment used are all conventional reagents, methods and equipment in the technical field unless otherwise specified.
[0025] For the sake of simplicity, this document only specifically discloses some numerical values and optional ranges. However, any lower limit can be combined with any upper limit to form an unambiguous range; and any lower limit can be combined with other lower limits to form an unambiguous range. Similarly, any upper limit can be combined with any other upper limit to form an unambiguous range; the optional items in the optional range can also be combined arbitrarily.
[0026] Unless otherwise specified, the terms used in this application have the commonly known meanings generally understood by those skilled in the art. Unless otherwise specified, the numerical values of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art.
[0027] The abbreviation PEDOT used in the present application is short for poly(3,4-ethylenedioxythiophene).
[0028] The present application provides a positive electrode material, the positive electrode material includes a ternary NCM material, the surface of the ternary NCM material is coated with Co 2+ / conductive polymer material to form a modified ternary NCM material.
[0029] The present application also provides a method for preparing a positive electrode material, wherein a modified ternary NCM material is prepared by mixing and reacting a ternary NCM, a cobalt-containing material and a conductive polymer.
[0030] In some embodiments, the reaction process is to mix the reaction raw materials ternary NCM, cobalt-containing material and conductive polymer in water, react at a high temperature of 180° C.-200° C., and the reaction time is 20-24 hours.
[0031] The conductive polymers in the present application include, but are not limited to, poly(3,4-ethylenedioxythiophene), polyaniline, polypyrrole, poly(p-phenylene glycol), and the like.
[0032] In some embodiments, the conductive polymer is poly(3,4-ethylenedioxythiophene) to form a Co 2+ / PEDOT; the mass ratio of ternary NCM to poly(3,4-ethylenedioxythiophene) is in the range of 30 to 34:1.
[0033] The cobalt-containing materials in the present application include but are not limited to: cobalt sulfate, cobalt chloride, cobalt hydroxide, cobalt carbonate, etc.
[0034] In some embodiments, the cobalt-containing material is cobalt sulfate; the mass ratio of the ternary NCM to CoSO4.7H2O is in the range of 16 to 20:1.
[0035] In some embodiments, after the ternary NCM, the cobalt-containing material and the conductive polymer mixture react at high temperature, they are subjected to process treatments, such as centrifugal washing and vacuum drying, to obtain a modified ternary NCM material product.
[0036] The present application provides a positive electrode plate, which includes a positive electrode active material, and the positive electrode active material includes the positive electrode material of the present application or the positive electrode material prepared by the method of the present application.
[0037] The battery containing the positive electrode material of the present application may be a lithium ion battery, a sodium ion battery, etc. In general, the battery of the present application may include a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, the active ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The present application has no special restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid. The separator is arranged between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, and at the same time allow ions to pass through. The present application has no special restrictions on the type of separator, and any known porous structure separator with good chemical stability and mechanical stability can be selected. The present invention does not specifically limit the positive electrode sheet, negative electrode sheet, electrolyte and separator of the above-mentioned battery.
[0038] When the positive electrode material of the present application is used to prepare the positive electrode sheet, a conventional preparation method can be adopted, and a binder and a conductive agent used in the art can be used. The ratio of the positive electrode material to the binder and the conductive agent can be obtained by a person skilled in the art through experiments.
[0039] The present application provides a battery, which adopts the positive electrode plate of the present application.
[0040] In some embodiments, the batteries of the present application may be assembled into a battery module. The number of batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0041] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0042] The present application provides an electrical device, which uses the battery of the present application.
[0043] In an electrical device containing the battery of the present application, the battery can be used as a power source for the electrical device or as an energy storage unit for the electrical device. The electrical device may include mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc., but is not limited thereto; as an electrical device, the battery can be selected according to its usage requirements.
[0044] The present invention is further described in detail below in conjunction with specific embodiments:
[0045] Embodiment 1:
[0046] 1. Preparation of modified NCM811
[0047] Dissolve NCM811, CoSO4.7H2O and poly (3,4-ethylenedioxythiophene) PEDOT in pure water, stir evenly, transfer it to a reactor, bake it at 180℃-200℃ for 20-24h, centrifuge and wash it, and vacuum dry it at 60℃ for 20-24h to obtain modified NCM811. The mass ratio of NCM811 to CoSO4.7H2O is 18:1, and the mass ratio of NCM811 to PEDOT is 32:1. Co is formed on the surface of NCM811. 2+ / PEDOT coated.
[0048] 2. Preparation of positive electrode slurry:
[0049] The positive electrode active material is NCM811 modified with the product obtained in step 1, the binder is PVDF (Kureha, KF1100), and the conductive agent is Super P (Swiss Termeco); the mixture is stirred and mixed in a mass ratio of active material: binder: conductive agent = 95.0:2.2:2.8, and after mixing evenly, it is coated on a 13um aluminum foil and dried in a vacuum drying oven at 120°C for 12h.
[0050] 3. Assembly of button batteries:
[0051] The button battery shell uses the CR2032 model, the diaphragm uses a 20um diaphragm, and the electrode uses a positive electrode with a uniform coating. In a glove box filled with argon, the button battery is assembled in the following order: battery shell - place the positive electrode - drip the electrolyte - place the diaphragm - drip the electrolyte - place the lithium sheet - place the gasket spring - battery shell.
[0052] 4. Cycle performance test:
[0053] A button battery charge and discharge tester (Wuhan Blue Electric, CT2001A) was used to perform 50 cycles of 0.2C charge and discharge tests on the button battery with a voltage range of 3.0-4.5 V. The test results are shown in Table 1.
[0054] 5. Test of pole piece peeling force:
[0055] Take the positive electrode sheet prepared in step 3, cut a sample of 15cm*5cm in size, fix it on a steel plate, fix the steel plate and the sample in the sample test area of the peel force tester, set the speed to 200mm / min, the test distance to 200mm, start the equipment, and read the data after the test is completed. The test results are shown in Table 1.
[0056] Embodiment 2:
[0057] It is basically the same as Example 1, except that the mass ratio of NCM811 to CoSO4.7H2O is 14:1.
[0058] Embodiment 3:
[0059] It is basically the same as Example 1, except that the mass ratio of NCM811 to CoSO4.7H2O is 16:1.
[0060] Embodiment 4:
[0061] It is basically the same as Example 1, except that the mass ratio of NCM811 to CoSO4.7H2O is 20:1.
[0062] Embodiment 5:
[0063] It is basically the same as Example 1, except that the mass ratio of NCM811 to CoSO4.7H2O is 22:1.
[0064] Embodiment 6:
[0065] It is basically the same as Example 1, except that the mass ratio of NCM811 to PEDOT is 28:1.
[0066] Embodiment 7:
[0067] It is basically the same as Example 1, except that the mass ratio of NCM811 to PEDOT is 30:1.
[0068] Embodiment 8:
[0069] It is basically the same as Example 1, except that the mass ratio of NCM811 to PEDOT is 34:1.
[0070] Embodiment 9:
[0071] It is basically the same as Example 1, except that the mass ratio of NCM811 to PEDOT is 32:1.
[0072] Comparative Example 1:
[0073] The method is basically the same as Example 1, except that no CoSO4.7H2O is introduced in step 1.
[0074] Comparative Example 2:
[0075] The process is basically the same as Example 1, except that no PEDOT is added in step 1.
[0076] The test and evaluation results of each embodiment and comparative example are as follows:
[0077] Table 1 Test results of embodiments and comparative examples
[0078] serial number Cycle performance Pole peeling force Example 1 93.8% 23.8N / m Example 2 91.1% 17.9N / m Example 3 91.5% 18.5N / m Example 4 91.4% 18.2N / m Example 5 91.4% 17.6N / m Example 6 90.5% 16.5N / m Example 7 90.8% 17.8N / m Example 8 91.4% 17.4N / m Example 9 90.1% 16.3N / m Comparative Example 1 84.1% 9.6N / m Comparative Example 2 81.3% 8.5N / m
[0079] From the test results, we can know that:
[0080] The cycle performance and electrode peeling force of Example 1 of the present invention are better than those of Examples 2-9, and more significantly better than those of Comparative Examples 1 and 2. The present invention has found that by using modified NCM material as the positive electrode material and introducing Co 2+ The cycle stability of traditional NCM can be improved; further research has found that the present invention can not only improve the conductivity of the positive electrode material by introducing a conductive polymer, but also simultaneously improve the pole piece peeling force between the active material and the aluminum foil; and unexpectedly, under the joint action of the conductive polymer and the cobalt-containing material, the cycle performance and the pole piece peeling force can be significantly improved, producing a synergistic effect; the process of this solution is simple, but the effect is obvious, and it is worthy of promotion and application.
[0081] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any technician familiar with the profession, without departing from the scope of the technical solution of the present invention, according to the technical essence of the present invention, any simple modification, equivalent replacement and improvement made to the above embodiment still falls within the protection scope of the technical solution of the present invention.
Claims
1. A positive electrode material, characterized in that: The positive electrode material includes a ternary NCM material, and the surface of the ternary NCM material is coated with Co 2+ / conductive polymer material to form a modified ternary NCM material.
2. The method for preparing the positive electrode material according to claim 1, characterized in that: The modified ternary NCM material is prepared by mixing and reacting the ternary NCM, the cobalt-containing material and the conductive polymer.
3. The method for preparing the positive electrode material according to claim 2, characterized in that: The reaction process is to mix the reaction raw materials ternary NCM, cobalt-containing material and conductive polymer in water, react at a high temperature of 180°C-200°C, and the reaction time is 20-24 hours.
4. The method for preparing the positive electrode material according to claim 2, characterized in that: The conductive polymer is at least one of poly(3,4-ethylenedioxythiophene), polyaniline, polypyrrole and poly(p-phenylene glycol).
5. The method for preparing the positive electrode material according to claim 2, characterized in that: The conductive polymer is poly(3,4-ethylenedioxythiophene), the mass ratio of the ternary NCM to poly(3,4-ethylenedioxythiophene) is in the range of 30 to 34:1, and Co is formed on the surface of the ternary NCM material. 2+ / PEDOT.
6. The method for preparing the positive electrode material according to claim 2, characterized in that: The cobalt-containing material is at least one of cobalt sulfate, cobalt chloride, cobalt hydroxide and cobalt carbonate.
7. The method for preparing the positive electrode material according to claim 2, characterized in that: The cobalt-containing material is cobalt sulfate, and the mass ratio of the ternary NCM to CoSO4.7H2O is in the range of 16 to 20:
1.
8. A positive electrode plate, characterized in that: The positive electrode sheet comprises a positive electrode active material, and the positive electrode active material comprises the positive electrode material according to claim 1 or a positive electrode material prepared by the method according to any one of claims 2 to 7.
9. A battery, characterized in that: The battery adopts the positive electrode sheet described in claim 8.
10. An electrical device, characterized in that: The electrical device uses the battery according to claim 9.
Citation Information
Patent Citations
Preparation method of lithium cobalt oxide positive electrode material coated with silicon-modified conducting polymer
CN104538599A
High-security double-coated Ni-Co lithium manganite anode material and preparation method thereof
CN107394166A
Preparation method and application of metal shell layer-coated surface composite positive electrode material
CN108063257A
Composite coated modified lithium ion battery cathode material and preparation method thereof
CN108511744A
Modifying method for high-nickel NCM ternary cathode material
CN109160546A